2019
DOI: 10.3390/pathogens8010038
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Genotyping Method for Rapid Differentiation of Blastocystis Subtypes and Subtype Distribution of Blastocystis spp. in Thailand

Abstract: Blastocystis spp. is one of the most common protozoa of humans and animals worldwide. The genetic diversity of Blastocystis spp. might be associated with a wide range of symptoms. However, the prevalence of each subtype is different in each country. Until now, there is no standard method for subtyping of Blastocystis spp. We developed a sequential restriction fragment length polymorphism (RFLP) analysis for the rapid differentiation of human Blastocystis subtypes. A large-scale study was also conducted to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 56 publications
2
12
1
Order By: Relevance
“…Our finding that ST3 was the predominant Blastocystis subtype was similar to the results of previously reported studies in Thailand [24,42,46,47] and other countries such as Japan, Bangladesh, Pakistan [38], and China [48]. Contrarily, other studies found that Blastocystis ST1 was the most predominant subtype [49,50].…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that ST3 was the predominant Blastocystis subtype was similar to the results of previously reported studies in Thailand [24,42,46,47] and other countries such as Japan, Bangladesh, Pakistan [38], and China [48]. Contrarily, other studies found that Blastocystis ST1 was the most predominant subtype [49,50].…”
Section: Discussionsupporting
confidence: 91%
“…However, ST3 was not the most common subtype in the Indigenous Tapirapé ethnic group in Brazil, which was considered to be related to little contact between indigenous groups and people in other communities [20]. In the present study, three subtypes (ST1, ST3 and ST4) were identified in two ethnic groups, and ST3 was the most common in Yao people (8/12, 66.67%) and in Wa people (5/10, 50%), which was similar to findings previously reported in almost all the studies in China (Table 4) [18,19,41,49,50,[53][54][55][56][57], and in some studies in a nearby country (Thailand) [25,28,37,52]. Minor subtypes (ST5-ST9 and ST12) that are only very rarely found in humans also show differences in geographical distribution.…”
Section: Discussionsupporting
confidence: 86%
“…To date, several methods based on specific primers for determining subtypes of Blastocystis sp. have been developed [ 60 , 70 , 111 115 ]. However, only a few of these methods can be used to determine mixed subtypes [ 111 , 113 , 115 , 116 ].…”
Section: Discussionmentioning
confidence: 99%